Perlindungan Purna Bekerja Bagi Pekerja Migran Indonesia Yang Bekerja Di Luar Negeri Berdasarkan Undang-Undang Nomor 18 Tahun 2017 - Ratni Sakina, Baiq Fadlin; Husni, Lalu (Faculty of Law, University of Mataram, 2024)
This research aims to analyze the form of post-employment protection for Indonesian migrant workers based on Law Number 18 of 2017 and analyze the suitability of this protection with the principles of social justice contained in Law Number 18 of 2017. The research method used is normative. The types of legal materials used are primary and secondary. The technique for collecting legal materials uses documentation techniques, which are analyzed deductively. The results of this research in the form of protection for Indonesian migrant workers after work are contained in Article 24 paragraph (1) of Law Number 18 of 2017, Government Regulation Number 59 of 2021 and BP2MI Regulation Number 6 of 2023. Apart from that, there are international regulations regarding migrant workers. In the ILO Conventions, especially the Labor Migration Convention (Revised Edition) 1949 and the Migrant Workers (Additional Provisions) Convention 1975. Protection after work in Article 24 Paragraph 1 of Law of the Republic of Indonesia Number 18 of 2017 concerning Indonesian Migrant Workers still does not reflect the principles of social justice, which emphasizes aspects of equality, non-discrimination, and balance between rights and obligations because this protection only focuses on procedural PMI without involving non-procedural PMI.